Identification and purification of human induced pluripotent stem cell-derived atrial-like cardiomyocytes based on sarcolipin expression. - Rebecca Josowitz (PLoS ONE, 2014)
The use of human stem cell-derived cardiomyocytes to study atrial biology and disease has been restricted by the lack of a reliable method for stem cell-derived atrial cell labeling and purification. The goal of this study was to generate an atrial-specific reporter construct to identify and purify human stem cell-derived atrial-like cardiomyocytes. We have created a bacterial artificial chromosome (BAC) reporter construct in which fluorescence is driven by expression of the atrial-specific gene sarcolipin (SLN). When purified using flow cytometry, cells with high fluorescence specifically express atrial genes and display functional calcium handling and electrophysiological properties consistent with atrial cardiomyocytes. Our data indicate that SLN can be used as a marker to successfully monitor and isolate hiPSC-derived atrial-like cardiomyocytes. These purified cells may find many applications, including in the study of atrial-specific pathologies and chamber-specific lineage development.